An international study about the factors that influence the success of co-branding from the consumer's perspective : The interactions between consistency and product categories - Liverani, Loris (My University, 2022)
This paper focuses on the analysis of strategic collaborations between companies, with a case study on co-branding between brands belonging to the sports and music industries. The choice of this topic is based on a twofold motivation: it is important to understand how the phenomenon of internationalisation and the dynamism of markets has led companies to collaborate more in order to maintain their competitive advantage, to be able to better face the crisis that has hit the world economy and to understand how alliances are fundamental for survival in highly innovative and competitive sectors. However, it is equally important to understand why partnerships are considered true instruments of innovation and growth, analysing them in detail, from the moment of their formation to their conclusion. The study focuses then, on the customer and the factors that impact his opinion of a co-branded offer in particular. The study's findings reveal significant discrepancies between Finnish, Italian, and Spanish customers. Finally, the study demonstrates that customers perceptions of brand coherence and their purchase behavior are positively influenced.
Keywords: fi=Markkinointi|en=Marketing|; Master's Degree Programme in International Business